MEMAHAMI KARYA SASTRA POSTMODERN MELALUI PEMBACAAN DEKONSTRUKSI DERRIDA - Ratun Untoro (Widyariset, 2009)
Literature has a spesific charachter. It informs many things to various kinds of readers. Postmodern literature art as a new genre brings impact on the ambiguity of meaning because of the logocentrism rejection. As a product of postmodern literature, Danarto 's literature work tries to deconstruct the convention about signifier and signified. Postmordern is to deconstruct the construction to create a new comfortable construction. The latest phenomena of literature progression of dark poetry, experimental poetry, minimalist poetry, and Danarto 's short story tend to ignore the stucture. It is hard to apreciate those literature works by applying modern theory. The appropiate theory to explore the meaning is deconstruction of Derrida.